Integrating an Engineering Library's Public Services Desk: Multiple Perspectives. - Jill Powell; Marybeth Michelson-Thiery; Linda Bryan (Issues in Science and Technology Librarianship, 2007)
Launching a new outreach initiative and renovating the library provide both an incentive and an opportunity to redesign service points and reexamine how staff can best meet the needs of their users. The Engineering Library at Cornell University recently merged separate reference and circulation desks into a single service area for a number of reasons. This process was made smoother by integrating the multiple perspectives and concerns of those affected by the change. The help of a staff development specialist, team building exercises, small cross-functional working groups, and provisions for cross training were all built into the process. Considering all points of view was an essential part of the process and its outcomes. [ABSTRACT FROM AUTHOR]